A Psychoanalysis on the Main Character in Franz Kafka “Metamorphosis” (1915) - Istiqomah, Risqiah Nurul; Fatmasari, Yuniar (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2025)
The purpose of the thesis is to find out the Id, Ego, and Superego of the main characters, that is, Gregor Samsa, the traveling salesman who transforms into a giant insect, and Metamorphosis, written by Franz Kafka and published in 1915. The method used in this study is descriptive-qualitative. The technique of collecting data is reading the novel repeatedly and underlying the necessary lines and quotations in the novella. The result shows that there are 24 quotations, which consist of 9 quotations of Id, 6 quotations of Ego, 7 quotations of Superego, and 2 most prominent reflections on Kafka’s personal life.